A study on the relationship between corpotare social responsibility (CSR) and employee commitment among non-academic staff in UiTM Jengka, Pahang / 'Atiyah Nurul Ain Amri - Amri, 'Atiyah Nurul Ain (Faculty of Business and Management, 2018)
This study was carried out to identify the factor that influences employee commitment in UiTM Jengka, Pahang. In chapter one, the researcher discussed about the background of the study. This research is study about the CSR as the independent variables toward employee commitment as the dependent variables. The objectives of this study are to identify the level of awareness of corporate social responsibilities among employee and to determine the relationship between corporate social responsibilities and the employee commitment. For the chapter three, methodology use for this research has been discussed. The methodology is method used by the researcher in finding the result while completing this research. This is including research design, sampling frame, population, sampling technique, and sample size, unit of analysis, instrument, and validity of instrument, data collection procedures and plan of data analysis. The researcher use convenience sampling technique. The scope of study only revolves within the organization and chooses workers from the certain department as respondent for the research. The research chooses workers from UiTM Jengka, Pahang as a scope of the study.